Hubungan Fear of Missing Out (FOMO) dengan Pola Nongkrong Anak Muda di Coffee Shop Kota Palangkaraya - Sabani, Ahmad; Larisa, Naila Isabel; Rhama, Bhayu (Institut Agama Hindu Negeri Gde Pudja Mataram, 2025)
This study aims to analyze the relationship between Fear of Missing Out (FOMO) and the hanging-out behavior of young people in coffee shops in Palangka Raya City. The increasing trend of spending time in coffee shops among youth is not solely driven by face-to-face social interaction needs but also by the desire for digital visibility and social recognition on social media platforms. This research employed a quantitative approach with a correlational design. The sample was selected using a purposive sampling technique and consisted, of respondents aged 18–25 years who actively visit coffee shops and use social media. Data were collected using a Likert-scale questionnaire and analyzed through correlation tests to examine the relationship between variables. The results show a positive and significant relationship between FOMO and hanging-out behavior (r = ___; p < 0.05), indicating that higher levels of FOMO lead to stronger tendencies among young people to spend time in coffee shops. These findings suggest that hanging out is not merely motivated by social interaction needs but also by the desire to maintain digital presence and social connectivity. This study contributes to understanding youth behavior in the digital era and provides insights for future research on contemporary social and cultural dynamics.